Resiliensi Pasien Pre Operasi Katarak di Instalasi Bedah Sentral - Marta, Ayu Putu; Tukan, Ramdya Akbar; Wijayanti, Dewi; Lesmana, Hendy; Pujianto, Ahmat; Iskandar, Ayuk Cucuk (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT The resilience of patients undergoing cataract surgery will have an impact on the patient’s ability to recover and heal after facing surgery. A Patient facing surgery that will be undergone requires high endurance, strong confidence to recover and remain productive after undergoing surgery. This study aimed to describe the resilience of pre-surgery cataract patients at the Central Surgical Installation of dr. H. Jusuf SK Hospital North Kalimantan Provincial Government. This design of research is descriptive. This study used purposive sampling techniques with a total of 81 respondents. The data collection method used a resilience questionnaire. Data analysis techniques used univariate analysis, namely frequency test. The result of this study showed that the resilience of pre surgery cataract patients has a minimum – maximum value of 30-40 which mean the patient’s resilience value was high. The results showed that the patient felt ready and comfortable while undergoing cataract surgery. Patients showed a high value resilience by not feeling depredded before undergoing cataract surgery and they can adapt to the changes that will occur after cataract surgery. Optimizing the role of nurses ang providing support to patient is one of efforts to maintain the nurse motivation in improving the quality of patient life. Keywords: Cataract, Preoperative, Resilience  ABSTRAK Ketahanan pasien yang menjalani operasi katarak akan berdampak pada kemampuan pasien untuk pulih dan sembuh setelah menghadapi operasi. Seresponden pasien menghadapi operasi yang akan dijalani membutuhkan daya tahan tubuh yang tinggi, kepercayaan diri yang kuat untuk pulih, dan tetap produktif setelah menjalani operasi. Penelitian ini bertujuan untuk mendeskripsikan resiliensi pasien pre operasi katarak di Instalasi Bedah Sentral RSUD dr. H. Jusuf SK Pemerintah Provinsi Kalimantan Utara. Desain penelitian ini adalah deskriptif. Penelitian ini menggunakan teknik purposive sampling  dengan jumlah responden 81 responden. Metode pengumpulan data menggunakan kuesioner resiliensi. Teknik analisis data menggunakan analisis univariat yaitu uji frekuensi.  Hasil penelitian ini menunjukkan bahwa resiliensi pasien pra operasi katarak memiliki nilai minimal -maksimum 30-40 yang berarti nilai resiliensi pasien tinggi. Hasil menunjukkan bahwa pasien merasa siap dan nyaman saat menjalani operasi katarak. Pasien menunjukkan nilai resiliensi yang tinggi dengan tidak merasa tertekan sebelum menjalani operasi katarak dan dapat beradaptasi dengan perubahan yang akan terjadi setelah operasi katarak. Mengoptimalkan peran perawat dan memberikan dukungan kepada pasien merupakan salah satu upaya untuk menjaga motivasi perawat dalam meningkatkan kualitas hidup pasien. Kata Kunci: Katarak, Pre Operasi, Resiliensi